Workshop Penguatan Interaksi Sosial dan Kepekaan Sosial dalam Permainan Tradisional Bentengan pada Anak Laki-Laki di Yayasan Panti Asuhan Sultan Suriansyah - Fauzi, Zainal; Hayati, Sri Ayatina; Kodriyah, Lailatul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The traditional game "Bentengan" plays an important role in the development of social interaction and social sensitivity in children, especially boys. This game involves two groups trying to attack and defend their "fortress," thus encouraging teamwork, effective communication, and joint strategies. The solutions offered by the implementers of this community service activity are: 1) Providing an understanding to the boys at the orphanage about good social interaction and how to behave in a sensitive manner to the environment around the orphanage, 2) A Workshop on Strengthening Social Interaction and Social Sensitivity in the Traditional Game "Bentengan" is expected to be the right solution by providing an educational playing experience and training children's social skills naturally. This activity was carried out for 2 times with various methods such as lectures, demonstrations, experiential methods, interactive discussion methods, observation methods where the facilitator team observed the dynamics of social interaction during the game, and participatory evaluation methods. The target audience for this activity was 20 children from the male orphanage at the Sultan Suriansyah Foundation in Banjarmasin.